Oncostatic mechanisms of melatonin and analysis of 8-oxoguanine by gas chromatography mass spectrometry - Scott, Aaron, author; Reif, John S., advisor; Cosma, Greg, committee member; Wells, Robert, committee member; Gardner, Henry, Jr., committee member; Campain, Julie A., committee member (Colorado State University. Libraries, 1999)
Melatonin studies have previously demonstrated the hormone to inhibit growth of estrogen receptor positive breast cancer cells after in vitro treatment through mechanisms not clearly understood. Chapter 1 experiments herein described a novel mechanism of cytotoxicity in MCF-7 human breast carcinoma cells through a mechanism disrupting mitochondrial bioenergetic pathways after less than 24 hours of treatment in estrogen extracted medium. Cell numbers were decreased to 40% of controls with morphologic and biochemical studies demonstrating acute cell death and increased electron transport activity accompanied by decreased cellular ATP levels. Estradiol rescued cells from the melatonin toxicity. Chapter 2 presented experimental evidence of differentiation in MCF-7 cells following melatonin treatment. Specifically, morphologic changes such as single nucleoli, decreased pseudopodia, and increased numbers and size of intermediate filament bundles were present as well as significantly increased numbers of cornified envelopes. Chapter 3 described laboratory bioassay methodology for clinical aspirates of gross fibrocystic breast disease fluid treatment of MCF-7 cells. The studies presented a novel finding of melatonin in the cyst fluids and explored the correlation of the hormone concentration to cell growth in a bioassay as well as biochemical endpoints. Interestingly, the results of this preliminary study suggested that melatonin concentration in breast cysts directly modulated MCF-7 cell growth. Finally, TGFβ levels in the culture medium from treated cells was also significantly related to MCF-7 cell number. Section II studies evaluated an internal standard method for the analysis of 8-oxoguanine by gas chromatography mass spectrometry. Additionally, an isotope dilution method with modifications and improvements over previously published procedures was described with the addition of quality control and quality assurance (QC/QA) data. In brief, the isotope dilution analysis demonstrated a sensitivity of 20 femptomoles, precision of 6.9%, and recovery accuracy of 99.7%. Chromatograms from the studies described column degeneration along with QC/QA recommendations to avoid error from this problem. Oxidation artifact was quantified and found as high as 1.1% of total guanine. Finally, room temperature derivatization was shown to be effective and precise with a 50% decrease in oxidation artifact. Surprisingly, addition of the antioxidant, ethane thiol, resulted in increased oxidation artifact.
Keywords: oncology; cellular biology; analytical chemistry